Selling a Story: A Case Study of Five Book Covers for Victor Pelevin’s Generation “P” (Imaginations: Journal of Cross-Cultural Image Studies, 2021)
In this article, book-cover design is studied in relation to translation and marketing. The discussion is centered on a case study of the Russian, British, American, Danish, and Norwegian editions of Victor Pelevin’s Generation “P” (Babylon in the U.K. and Homo Zapiens in the U.S.). The analysis of the book covers focuses on marketing strategy and argues that the cover of a translation affects how a novel is read and understood in the target culture.
Keywords: translation; book cover design; book marketing